The teaching of medicine at Universidad del Valle (Colombia Medica, 2010)
The first formal attempt for medical education in Valle del Cauca was in the Faculty of Medicine and Surgery in Buga, which was part of the Colegio Académico between 1866 and 1871. It only had one graduating class of ten physicians in 1871. Its foundation was contemporaneous with the faculties of medicine at Universidad de Antioquia and Universidad del Cauca; the reasons for its prompt disappearance are unknown. The professional training concerns of the región were maintained through the creation of the Sociedad de Medicina del Cauca (Cauca Medical Society) in 1887, which gave rise to the Boletín de Medicina del Cauca (Cauca Medical Newsletter) (1887-1910) which published the works of Evaristo García and his partners Daniel Quijano Wallis, Pedro Pablo Scarpetta, Agustín Escobar, Enrique Garcés, Adolfo Tenorio, and Pablo García Aguilera, among others. The need to create a school of medicine in Cali was aired since the 1940s among trade groups at the Colegio Médico del Valle (Valle Medical School), although some thought that the warm climate in Cali was not suitable for intellectual development because such required cold environments like those in the Cundinamarca and Boyacá plateau. History managed to reveal how wrong these believers of geographical determinism were. The Humphreys Mission, commissioned by the National Government in 1948, delivered a bleak report (1950) on medical education in Colombia suggesting the creation of new medical faculties, among them one in Valle del Cauca. Guillermo Orozco, a physician from Anserma and living in Cali, with support from the Colegio Médico del Valle, managed to get the Governor, physician Antonio Lizarazo, to expedite Decree 641 of 1950, ordering the creation of a faculty of medicine affiliated to the recently created Universidad del Valle. The University had been founded in 1945 with the name of Universidad Industrial del Valle del Cauca; the name was changed in 1954 to Universidad del Valle when the Dean of Medicine, Dr. Velásquez, was designated Departmental Secretary of Education. With support from Carlos Arturo Cabal, then Rector of the University, in November 1950, the Governor named Dr. Gabriel Velásquez Palau, a physician from Cali, as Dean of Medicine. Classes began on the 12th of October of 1951 with fifty students at the former convent of San Agustín already converted to Colegio de Santa Librada, located in Carrera 4 with calle 13; the medical practices took place at the San Juan de Dios Hospital. Excited by the collective dream of accomplishing a change in medical education, prestigious professors started arriving in Cali from many latitudes like Jorge Araújo Grau, Luis María Borrero, Plutarco Naranjo, Pelayo Correa, Carlos Restrepo, Jorge Escobar Soto, Miguel Gracián, Jaime Korgi, Carlos León, Lupi Sergio Mendoza, Santiago Rengifo, Vicente Rojo, and Carlos Sanmartín, among others. This group of adopted «Caleños» joined prestigious local physicians, many of them trained abroad with support from the Kellogg and Rockefeller Foundations, until forming a critical mass, a sort of athenaeum of the enlightened, which would change the Colombian and Latin American educational model, and even influence on the global educational model.